2017
DOI: 10.1002/pro6.20
|View full text |Cite
|
Sign up to set email alerts
|

Study on the correlation of serum amyloid A level with overall survival and radiation pneumonitis in non‐small cell lung cancer patients receiving thoracic radiotherapy

Abstract: Objective: Serum amyloid A (SAA) is a non-specific acute phase reaction protein that shows much higher levels in patients with cancer than in healthy individuals. The present study was designed to investigate the correlation of SAA level with overall survival (OS) and radiation pneumonitis (RP) in non-small cell lung cancer patients receiving thoracic radiotherapy. Methods:Patients with locally advanced non-small cell lung cancer receiving thoracic radiotherapy or concurrent chemoradiotherapy were eligible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Interestingly, we found that saliva in HNC patients demonstrated upregulated levels of serum amyloid A-1, while this protein was not found in tear fluid. The serum amyloid proteins have powerful pro-inflammatory and cytokine-like properties, and have been found to be highly expressed in a number of malignancies [ 24 , 25 ]. Thus, this protein could play a role in the acute and late effects of RT, and the upregulated levels in saliva as compared to tears may be a consequence of the lower radiation dose received by the lacrimal glands.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we found that saliva in HNC patients demonstrated upregulated levels of serum amyloid A-1, while this protein was not found in tear fluid. The serum amyloid proteins have powerful pro-inflammatory and cytokine-like properties, and have been found to be highly expressed in a number of malignancies [ 24 , 25 ]. Thus, this protein could play a role in the acute and late effects of RT, and the upregulated levels in saliva as compared to tears may be a consequence of the lower radiation dose received by the lacrimal glands.…”
Section: Discussionmentioning
confidence: 99%